Prevalence of chronic kidney disease and metabolic related indicators in Mianzhu, Sichuan, China - Chen, Feng; Wang, Miao; Jiang, Yan (Frontiers in Public Health, 2024)
Background: Chronic kidney disease (CKD) is a major public health problem worldwide. Periodic surveys are essential for monitoring the prevalence of CKD and its risk factors. We assessed the prevalence of CKD and its risk factors in Mianzhu City in 2020.Method: The Natural Population Cohort Study surveyed 7,770 individuals aged＞20 years in Mianzhu City of Sichuan province in 2020. Our investigation encompassed the measurement of CKD prevalence, the evaluation of various renal function indicators, and comparisons based on age, gender, and hukou status. Additionally, some metabolic indices were also measured to identify the underlying causes of CKD.(1) Overall, the prevalence of reduced renal function (eGFR＜60ml/min/1.73m 2 ), albuminuria, and CKD were 1.3%, 10.0%, and 10.4%, respectively. (2) The overall prevalence of CKD was higher among men than among women (14.5% vs. 8.6%). Similarly, the prevalence of CKD was higher among men than women in most age groups.(3) Among urban residents, the prevalence of CKD was higher among middle-aged individuals and lower among young individuals and older adults. (4) Considering eGFR, the albuminuria and CKD for group definition, Blood pressure, triglyceride, high-density lipoprotein, blood sugar, and BMI were all statistically different among between normal groups and abnormal groups s in the albuminuria and CKD.The incidence of CKD greatly varied between Mianzhu City and other regions in China and other countries. The differences in risk factors of CKD should be explored in the future. The gender difference in the prevalence of CKD in this study was markedly different from that in previous studies. More high-quality studies are needed to further explore this controversy. Based on the different prevalence of CKD and metabolism-related indices in rural and urban areas in this study, we speculated that the high incidence of CKD in Mianzhu City might be related to diet, lifestyle, and availability of healthcare services.